Improving Learning Outcome Through Mind Mapping Learning Model in International Trade Law at STHB - Meliyani Sidiqah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
International trade law is one of subjects at Sekolah Tinggi Hukum Bandung (STHB) in semester VI. It provides some theories to be applied in the field, especially those related to international trade. Students must be able to apply the theories through case analysis. However, the problem found in the classroom is the students have difficulty understanding the materials so the learning outcomes are not satisfactory. This research is limited to the application of mind mapping models in international trade law and is limited to certain subjects, namely Class A students in semester VI at STHB for the Academic Year 2021/2022. The problems identified were related to the application of the mind mapping model in international trade law, and how much improvement in learning outcomes. This research is a Classroom Action Research (CAR). The approach is a mixed method. The research was conducted on a two-cycle CAR. The data used were from students of Class A.The data collection method is the observation method. The result of thisresearch is that the application of learning using the mind mapping model inthe international trade law course proved successful, and the increase inlearning outcomes was very high.